Space law in the context of three legal regimes. The unity of objectives or the egoism of interests? (Discourse of Law and Administration, 2022)
The article presents the current issues related to the use of outer space along with the necessity to comply with the applicable regulations establishing international space law. The process of the evolution of the use of space is presented. It starts with the monopoly of states, through actions of international organisations exercising the will of appropriate states and culminating with national space agencies, also providing the institutional support for private entities. The paper, taking into account the evidenced multitude of the entities involved, presents legal regulations in which the first conventions, agreements from the 1960s and 1970s, establishing jointly international space law, should be treated as ius cogens norms.
Keywords: international legal regulations of peaceful use of outer space; geostationary orbit; space exploration; space law - legal regimes; multitude of entities exploring space; state and non-state entities; national space agencies